IL-1β expression and change following SRP in gingival crevicular fluid in patients with periodontitis: a systematic review and meta-analysis - Wang, Juan; Liu, Qing; Yu, Jinpin; Li, Jialing; Chen, Bin; Dong, Yingchun (Penerbit Universiti Kebangsaan Malaysia, 2025)
Periodontitis is a chronic inflammatory periodontal lesion, characterised by progressive destruction of connective tissue and continuous loss of marginal bone surrounding the teeth. Cytokines and chemokines play a role in the pathogenesis of chronic periodontitis (CP). Among these, IL-1β is considered one of the most important inflammatory factors and tissue-destructive cytokines. Despite numerous investigations identifying the role of IL-1β in gingival crevicular fluid (GCF) in bone resorption and connective tissue destruction, the efficacy of GCF IL-1β in assisting the diagnosis and predicting the progression of CP remains undetermined. The objective of this study was to ascertain whether IL-1β can be used as a diagnostic and progressive biomarker for CP. To this end, GCF IL-1β levels were compared between periodontally healthy controls and subjects diagnosed with CP, as well as between subjects before and after scaling and root planning (SRP) for CP. Additionally, the correlations between GCF IL-1β levels and various clinical parameters, including probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), plaque index (PI), and gingival index (GI), were analysed within the CP group. A comprehensive search of the PubMed, Embase and Cochrane databases was conducted from their inception up to 1 April 2022. The electronic search terms employed were ‘periodontitis OR periodontal diseases’ AND ‘Interleukin-1β OR IL-1β’ AND ‘gingival crevicular fluid’. The review includes cross-sectional, case series, single arm studies, prospective and retrospective cohort studies, as well as randomised controlled trials (RCTs) and non-RCTs. The studies that compared IL-1β levels (either the concentration or the total amount) between healthy controls and subjects with CP, or between subjects with CP before and after SRP, were included in the review. The meta-analysis was conducted using Review Manager 5.3. The analysis included data from 50 studies comprising 1,502 patients. The concentration, total amount of GCF IL-1β, and GCF volume in subjects with CP were found to be significantly higher than in healthy controls (P < 0.01). The concentrations of GCF IL-1β in CP group decreased significantly at 1 month (P = 0.04), 1.5 months and 3 months following SRP compared with the preoperative baseline (P < 0.01). The total amounts of GCF IL-1β in CP group decreased significantly at postoperative 1 month, 1.5 months, 3 months, and 6 months compared with the baseline, and the P-values are all less than 0.01 except P =0.02 for 1.5 months. GCF volumes in CP group decreased significantly at 1 months, 3 months, and 6 months following SRP compared with the baseline (P < 0.01). The total amount of GCF IL-1β was found to be correlated positively and closely with BOP (r=0.894, P=0.041) in CP group. No significant correlations were identified between the total amount of IL-1β and other clinical parameters, nor between the concentration of IL-1β and any clinical parameter (P > 0.05). GCF IL-1β may serve as a diagnostic and progressive biomarker of chronic periodontitis (CP). The measurement of GCF IL-1β levels may prove beneficial in the diagnosis of initial periodontitis, the assessment of the therapeutic efficacy of SRP for CP, the determination of disease severity and activity, and the prediction of CP progression.